Gestión empresarial y la competitividad en los restaurantes turísticos en la región Loreto 2023 - Tuesta Chuquipiondo, Carlos Leandro (2025)
The purpose of the study was to determine the influence between business management and the competitiveness of tourist restaurants in the Loreto region, 2023. The research was of an applied type, with a non-experimental and simple correlational design and finally a quantitative approach was used. The study subjects were 150 restaurants in the Loreto region. The instrument was applied as a technique and the data were collected through a content validated questionnaire with a Cronbach's Alpha coefficient of 0.875. Subsequently, the data were analyzed using the statistical software SPSS version 25. The findings showed a high correlation greater than 70% between the variables studied. Which concluded that, if there is a significant influence between business management and the competitiveness of tourist restaurants in the Loreto region, reflected in a Spearman correlation coefficient of 0.785, which indicates a high positive correlation, with a level of statistical significance of p<0.05.